FRI0161 Sec16a Gene Deletion in A Large Axial Spondyloarthritis Family. (10th June 2014) - O'Rielly, D.D.; Uddin, M.; Mostafa, A.A.; Codner, D.; Hackett, D.; Haroon, N.; Inman, R.; Rahman, P.
Abstract : Background: Genetic factors are of major importance in susceptibility to ankylosing spondylitis (AS). Currently there are 43 genetic loci associated with AS pathogenesis but these only explain a small proportion of the heritability which suggests that other rare genomic variants may contribute as risk factors. Given that AS is a subset of axial spondyloarthritis, it too is likely to have a strong genetic component. Objectives: To identify novel rare, highly penetrant mutations associated with AxSpA segregating within well-characterized families. Methods: Samples were collected from affected and healthy individuals from a large multigenerational, well-characterized family with AxSpA with Northern European Ancestry. All AxSpA patients satisfied the ASAS classification. Full exome sequencing was performed on eleven family members using the Agilent SureSelect Human All Exon kit V4 for library preparation and exome enrichment and sequencing was performed on an Illumina HiSeq 2000 instrument with TruSeq sequencing chemistry V3. Variants of interest identified by exome sequencing were confirmed using Sanger sequencing. Gene expression profiling was performed using a Taqman Gene Expression Assay (Cat#4331182, SEC16A-Hs00389570_m1, GAPDH-Hs99999905_M1) and protein expression was assessed using Western analysis using a commercial SEC16A antibody. Results: Our family-based exome sequencing analysis revealed a 9-bp in-frame deletion in SEC16A which segregated with AxSpA in the family. This deletion was confirmed in extended family members with 7/9 of the clinically diagnosed AxSpA members carrying the SEC16A deletion using Sanger sequencing. All healthy (i.e., not diagnosed with AxSpA) family members did not carry the deletion. The in-frame deletion had no significant impact on gene or protein expression. Conclusions: Full exome sequencing of a large multigenerational AxSpA family revealed a 9-bp deletion in SEC16A segregating in the majority of affected family members. Although this in-frame deletion had no significant impact on gene or protein expression, a detrimental impact on protein structure of SEC16A remains a possibility and is currently under investigation. The association of this deletion within the SEC16A gene with AxSpA is particularly interesting given that the gene product plays a role in protein transport from the endoplasmic reticulum (ER) to the Golgi and mediates COPII vesicle formation at the transitional ER. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3327